Использование методов статистической физики для исследования экономико-производственных систем с массовым выпуском продукции - Демуцкий, Виктор Петрович; Пигнастый, Олег Михайлович; Ходусов, Валерий Дмитриевич; Азаренкова, М. Н. (Харківський національний університет ім. В. Н. Каразіна, 2005)
Построена математическая модель экономико-производственной системы с массовым выпуском продукции. Состояние производственной системы в любой момент задается точкой в ​​двумерном фазовом пространстве. Введена функция распределения для базового продукта и записано уравнение для этой функции. Получены уравнения для уравнений состояния для макроскопических параметров получаемой системы. Выписаны условия устойчивости функционирования производственной системы.

A mathematical model of mass production dynamics in engineering is constructed. The state of production system at any moment is given by a point in two-dimensional phase space. Distribution function for base product is introduced and the equation for this function is written. There is the analogy of kinetic equation in physics. The engineering-production and generative functions are defined. The equations for disturbance state of closed system of the state equations for macroscopic parameters of produced system are received. The stability conditions of function of produced system are written. The such interconnection between the surplus and the temp of moving of basic products along the technological chain which guarantees the stability of produced process function to be shown.
Use of statistical physics methods to investigate the economical production systems with repetition production
Keywords: синергетика; базовый продукт; микроскопическое описание; функция распределения; инженерно-производственная функция; генераторная функция; уравнения балансов; synergetic; basic product; macroscopic description; distribution function; engineering-production function; generative function; equations of balance